2014
DOI: 10.1166/jbn.2014.1763
|View full text |Cite
|
Sign up to set email alerts
|

Nanoformulation Improves Activity of the (pre)Clinical Anticancer Ruthenium Complex KP1019

Abstract: Ruthenium anticancer drugs belong to the most promising non-platinum anticancer metal compounds in clinical evaluation. However, although the clinical results are promising regarding both activity and very low adverse effects, the clinical application is currently hampered by the limited solubility and stability of the drug in aqueous solution. Here, we present a new nanoparticle formulation based on polymer-based micelles loaded with the anticancer lead ruthenium compound KP1019. Nanoprepared KP1019 was chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 0 publications
1
27
0
3
Order By: Relevance
“…Two typical Ru(III)-drugs [ImH][trans-RuCl 4 (DMSO)(Im)] (NAMI-A) and [IndH][trans-RuCl 4 (Ind) 2 ] (KP1019) have successfully entered clinical trials [24]. However, more detailed investigation of the antitumor mechanism of these ruthenium compounds still remains largely speculative [59].…”
Section: Introductionmentioning
confidence: 99%
“…Two typical Ru(III)-drugs [ImH][trans-RuCl 4 (DMSO)(Im)] (NAMI-A) and [IndH][trans-RuCl 4 (Ind) 2 ] (KP1019) have successfully entered clinical trials [24]. However, more detailed investigation of the antitumor mechanism of these ruthenium compounds still remains largely speculative [59].…”
Section: Introductionmentioning
confidence: 99%
“…Micelles delivering metallodrugs have been investigated [55][56][57][58][59][60]. One strategy involved the covalent attachment of the drug directly to the micelle to avoid its premature release in the circulation [55][56][57][58][59].…”
Section: Micellesmentioning
confidence: 99%
“…It was found that nanocomplexation of TMZ increased approximately twice its antipro- liferative activity. It could be due to the selectively increase of the drug accumulation in tumor cells and slow drug release into the interstitial space of the tumor [18,19]. Application of such kind of complex stimulates the cells to accumulate the drug by endocytosis pathway and by macropinocytosis pathway.…”
Section: Fig 7 Ratio Of Dead Cells Treated For 72 H With Free Temozmentioning
confidence: 99%